ANALISIS SKRINING FITOKIMIA, AKTIVITAS ANTIOKSIDAN, TOTAL FENOL-FLAVONOID EKSTRAK DAUN DAN BUAH TANAMAN GALAM RAWA GAMBUT (MELALEUCA CAJUPUTI ROXB) - Raden Roro Ariessanty Alicia Kusuma Wardhani; Okviyoandra Akhyar; Emilda Prasiska (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract.  The galam forest is a typical forest in South Kalimantan which is capable of growing on peat land. Generally, galam leaves are used as an herbal medicine and the fruits are used as a substitute for pepper as well as herbs additional material. Galam potential that can be used as herbs underlying the research done on phytochemical screening analysis, antioxidant activity and the fenol-flavonoid total level. Analysis was done to leaves and fruit ethanol extract of a galam plant. Compounds of secondary metabolite of alkaloid, polyphenol, quinone, flavonoid and saponin were found in galam leaves ethanol extract. Fruit ethanol extract contained compounds of  the polyphenol, quinone, flavonoid and saponin.  The total concentration of phenol from galam leaves and fruit ethanol extract were defined by using Folin-Ciocalteu method and the results were each 18,3615 ppm and 40,2926 ppm while the total of phenol level were as much as 16,52535 mg GAE/mg of extract and 36,26334 mg GAE/mg of extract . The total concentration of flavonoid was specified by using the method of AlCl3 and the values were 0,1146 ppm and 0,0076 ppm . The total levels of leaves and fruit extract flavonoid were as much as 0,3438 mg QE/g of extract and 0,0228 mg QE/g of extract. Antioxidant activity was specified by using DPPH (1,1-diphenyl-2- picrylhidrazyl) method with ascorbic acid as the comparison compounds. Antioxidant testing result showed that the values of leaves ethanol extract IC50 were 54,4906 ppm and 37,3752 ppm, while ascorbic acid was 9,887 ppm .